Social Integration in Young Adulthood and the Subsequent Onset of Substance Use and Disorders among a Community Population of Urban African Americans* - Green, Kerry M. (2010)
AIMS: This article examines the association between social integration in young adulthood and the later onset of substance use and disorders through mid-adulthood. DESIGN: Data come from a community cohort of African Americans followed longitudinally from age 6–42 with four assessment periods. SETTING: The cohort all lived in the Woodlawn neighborhood of Chicago in 1966, an urban disadvantaged setting. PARTICIPANTS: All Woodlawn first graders in 1966 were asked to participate; 13 families declined (N=1242). MEASUREMENT: Substance use was measured via interview at age 42 and includes the onset of alcohol and drug use disorders and the onset of cocaine/heroin use between ages 32 and 42. Social integration measures were assessed via interview at age 32 and include social roles (employee, spouse, parent), participation in religious and social organizations, and a measure of overall social integration. Control variables were measured in childhood and later in the lifecourse. FINDINGS: Multivariate regression analyses suggest that unemployment, being unmarried, infrequent religious service attendance, and lower overall social integration in young adulthood predict later adult-onset drug use disorders, but not alcohol use disorders once confounders are taken into consideration. Unemployment and lower overall social integration predict onset of cocaine/heroin use later in adulthood. CONCLUSIONS: Results show meaningful onset of drug use and substance use disorders during mid-adulthood and that social integration in young adulthood seems to play a role in later onset of drug use and drug disorders, but not alcohol disorders.